Comparison study on microstructure and mechanical properties of Sn-10Bi and Sn-Ag-Cu solder alloys and joints. (November 2017) - Guo, Qinhan; Zhao, Zhenjiang; Shen, Chunlong
Abstract: The comparison study of Sn-10Bi and Sn-3.0Ag-0.5Cu solder alloys and joints was conducted. The results showed that the liquidus of Sn-10Bi solder alloy was lower than that of Sn-Ag-Cu slightly. The interfacial IMCs layer growth of Sn-10Bi/Cu was slower than that of Sn-Ag-Cu/Cu during liquid/solid reaction. The higher strength and lower creep strain rate of Sn-10Bi comparing with that of Sn-Ag-Cu were contributed by the solid solution strengthening effect of Bi atom in β-Sn phase. The ultimate bending load of Sn-10Bi joint was higher than that of Sn-Ag-Cu joint as the high strength of Sn-10Bi solder alloy. Moreover, the thinner and more flat IMCs layer also ensured the stable maximum bending displacement of Sn-10Bi joint at a loading speed of 1 mm/s compared with that of Sn-Ag-Cu joint. Highlights: The liquidus of Sn-10Bi was found lower than that Sn-Ag-Cu. The growth rate of IMCs layer of Sn-10Bi/Cu was slower than that of Sn-Ag-Cu/Cu. The strength and creep performance of Sn-10Bi was better than that of Sn-Ag-Cu. The solid solution strengthening effect of Bi in β-Sn phase was notable.